2013
DOI: 10.1021/nl402053z
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Nanosponge Electroporation for Affordable and High-Efficiency Disinfection of Bacteria and Viruses in Water

Abstract: High-efficiency, affordable, and low energy water disinfection methods are in great need to prevent diarrheal illness, which is one of the top five leading causes of death over the world. Traditional water disinfection methods have drawbacks including carcinogenic disinfection byproducts formation, energy and time intensiveness, and pathogen recovery. Here, we report an innovative method that achieves high-efficiency water disinfection by introducing nanomaterial-assisted electroporation implemented by a condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(141 citation statements)
references
References 39 publications
(49 reference statements)
3
138
0
Order By: Relevance
“…The use of such geometries has shown advantages over the use of modified electrodes, such as minimizing the effects of pH condition and electrolysis on electroporation . Several other techniques incorporating nanowires and nanotubes to enable low voltage electroporation have also been reported . Recently, insulator‐based dielectrophoresis (iDEP) based microfluidic devices have shown many attractive advantages in single cell manipulations (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of such geometries has shown advantages over the use of modified electrodes, such as minimizing the effects of pH condition and electrolysis on electroporation . Several other techniques incorporating nanowires and nanotubes to enable low voltage electroporation have also been reported . Recently, insulator‐based dielectrophoresis (iDEP) based microfluidic devices have shown many attractive advantages in single cell manipulations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This equation is valid as long as the conductivity of cell membrane is of about several orders less than the conductivity of the buffer medium . In the literature, successful electroporation has been reported for lower conductive solutions such as DI water (0.055 µS/m) , city water (5 mS/m) , artificial buffer (1 mS/m, 5 mS/m, 0.14 S/m, and 1.6 S/m) , and other buffer (127 mS/m) . Pucihar reported that cell viability remains high for low conductive buffer whereas electro‐permeabilization remains unaffected .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18] Nevertheless, its hierarchical and high porosity with great mechanical durability make this material suitable for usage in both mechanical and chemical filters. 19,20 Moreover, easy surface modification of PU with both organic and inorganic materials helps to control of its wettability. 21,22 Taking those challenges and demands into consideration, herein, we propose a simple, but effective way to produce an advanced multifunctional composite by adopting polyurethane foam and thin layers coating of both organic and inorganic substances.…”
Section: Introductionmentioning
confidence: 99%
“…Although, electrochemical inactivation of viruses has demonstrated to be effective, bacteria have shown to be more vulnerable to this treatment than virus. Liu et al (2013) reported 2 log removal for MS2 and 6 log removal for e. coli, Salmonella enterica, Enterococcus faecalis, and Bacillus subtilis by applying 20 and 10 V, for virus and bacteria respectively (Liu et al 2013). Kerwick et al (2005) demonstrated that electrochemical disinfection at 5 V is effective against bacteriophage MS2 and e. coli (Kerwick et al 2005).…”
Section: Microorganism Referencementioning
confidence: 99%
“…The applied electric field should be enough to achieve the breakdown potential of the cell membrane (i.e., 800 kV cm -1 for a 5 nm membrane) (Liu et al 2013, Schoen et al 2010). This technique is commonly used in microbiology to insert DNA into a variety of cells (Figure 3) (Haas and Aturaliye 1999).…”
Section: Electroporation Principlementioning
confidence: 99%